Coupled polymer microfiber lasers for single mode operation and enhanced refractive index sensing - Ta, Van Duong (2014)
Single mode lasing operation is obtained from coupled whispering gallery mode polymer fiber lasers via the Vernier effect. This coupled structure offers a significant improvement in sensitivity (∼400 nm/refractive index unit) for refractive index sensing compared to a single cavity. These findings imply that polymer fibers are promising candidates for micro/nano-integrated photonic devices because of their mechanical flexibility and cost-effectiveness.